2012
DOI: 10.4161/epi.22070
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications and p21-cyclin B1 nexus in anticancer effect of histone deacetylase inhibitors in combination with silibinin on non-small cell lung cancer cells

Abstract: (2012) Epigenetic modifications and p21-cyclin B1 nexus in anticancer effect of histone deacetylase inhibitors in combination with silibinin on non-small cell lung cancer cells,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 41 publications
3
35
2
1
Order By: Relevance
“…Mateenet al observed that the treatment of small and nonsmall lung cancer cells with silibinininhibitedtheHDACi (histone deacetylase inhibitors) in NSCLC lung cancer cell line and increased in general the acetylation of histones H3 and H4. They further treated the cells with silibinin and HDACi and observed the expression of P21 (Mateen et al, 2012). Roy et al observed that silibinin increased the expression of P53, and activated the P21 as well.…”
Section: Discussionmentioning
confidence: 99%
“…Mateenet al observed that the treatment of small and nonsmall lung cancer cells with silibinininhibitedtheHDACi (histone deacetylase inhibitors) in NSCLC lung cancer cell line and increased in general the acetylation of histones H3 and H4. They further treated the cells with silibinin and HDACi and observed the expression of P21 (Mateen et al, 2012). Roy et al observed that silibinin increased the expression of P53, and activated the P21 as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that entinostat additionally induces growth inhibition itself through induction of cell cycle arrest genes (p21 Waf , GADD45), thereby blocking cell cycle progression, represented by the observed G1 arrest (BT474) or G2 arrest (SUM190). Previous studies have shown that enhanced p21 Waf levels induced by an HDAC inhibitor promoted proteasomal degradation of cyclin B1 and resulted in G2/M arrest [40] and that GADD45 promotes G2/M arrest via nuclear export and kinase activity of Cdc2 [41]. We observed that single treatment with entinostat appeared more effective in inhibiting growth than single treatment with lapatinib in soft agar culture.…”
Section: Discussionmentioning
confidence: 60%
“…The final concentration of DMSO in medium during different treatments did not exceed 0.1% (v/v). Compared with previous studies in which we assessed the cell growth inhibitory activity of silibinin (up to 75 mM concentration) in lung cancer cells (Mateen et al, 2010(Mateen et al, , 2012, here we chose relatively lower doses of silibinin (3.75-12.5 mM) so that silibinin alone or in combination with other drugs does not affect growth and death of NSCLC cells and thus could be used for future invasion and migration studies.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, silibinin, a nontoxic chemopreventive agent, has shown strong anticancer efficacy against NSCLC cells in culture and nude mice (Mateen et al, 2010), together with the potential to alter enzymatic activity and protein levels of HDACs in NSCLC cells (Mateen et al, 2012). Specifically, silibinin was found to inhibit HDAC activity and decrease HDAC 1-3 levels in NSCLC cells, leading to an overall increase in global histone acetylation states of H3 and H4 (Mateen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation